Plantlet regeneration from nodal explants of Ocimum citriodorum Vis. (Bangladesh Journal of Scientific and Industrial Research, 2013)
A protocol for multiple shoot induction and plant regeneration from nodal explants of Ocimum citriodorum has been developed. Nodal explants inoculated on Murashige and Skoog (MS) medium supplemented with 1.0 mg/l Benzyl adenine (BAP) and 0.025 mg/l indole -3- acetic acid (IAA) showed better growth response (80%) and produced 15.2 ± 1.28 shoots per explant with an average length of 6.17 ± 0.29 cm after 35 days. Roots were induced after transfer to half strength MS medium supplemented with 0.5 mg/l Indole -3- butyric acid (IBA) produced 6.0 ± 1.0 roots with an average height of 4.9 ± 0.26 cm after 30 days. Plantlets with well developed root and shoot systems were successfully acclimated (80 %) and established in earthen pots containing mixture of soil, vermiculite and farm yard manure (1:1:1). Bangladesh J. Sci. Ind. Res. 47(4), 433-436, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.8547